The Development of Flip Chart Media in the Indonesian Language Subject to Enhance Students' Reading Comprehension Skills at Elementary School - Mustakim, Mustakim; Putrayasa, Ida Bagus; Sudiana, I Nyoman (MANAZHIM, 2024)
The objectives of this research are as follows: 1) To explore the development of Flip Chart Media in the Indonesian language subject to improve reading comprehension skills at SDN 1 Sukarara; 2) To analyze the product of the development of Flip Chart Media in the Indonesian language subject in enhancing students' reading comprehension skills at SDN 1 Sukarara; 3) To identify the obstacles faced by teachers and students in implementing Flip Chart Media in the Indonesian language subject at SDN 1 Sukarara. The methods of this research utilized a research and development approach, referring to the Research and Development (R&D) model by Borg and Gall. The population in this study consists of the entire number of male and female students at SDN 1 Sukarara, totaling 251 students, and the research sample was the fourth-grade class, comprising 30 students. This research was conducted from October to December 2023. The product trial included the tested product, trial subjects, and the implementation of the trial. Data collection techniques employed were interviews, questionnaires, written tests, and documentation. Research instruments consisted of: a) Instruments for Subject Matter Experts; b) Instruments for Media Experts; c) Questionnaire Instruments for Students; and d) Student Evaluation Test Instruments. Data analysis was conducted through validation and trial steps by calculating the obtained scores. The data collected in this research were both qualitative and quantitative. The research findings are as follows: 1) Based on validation results, revisions, and evaluations, there was an improvement in the assessment of the developed product, specifically showing positive outcomes for the Interactive Indonesian Flip Chart Media. The development of this Flip Chart media used the Borg and Gall development model, simplified into 7 steps: needs analysis, design, prototype creation, product revision, field trials, final revision, and utilization; 2) Based on the analysis of expert team validation regarding the quality of the developed product, the Interactive Indonesian Flip Chart Media falls under the "good" category. Observations during the trial process also indicated that students were enthusiastic about learning when using the developed Interactive Indonesian Flip Chart Media. The delivery of material using Flip Chart media was easily understood by students. In terms of learning outcomes, the use of Interactive Indonesian Flip Chart Media also had an impact on students' reading comprehension skills in the Indonesian language. Based on the post-test results given to 30 students, 26 students (87%) passed and 4 students did not pass (23%), classified as "good" learning achievement. This indicates that the development of Interactive Indonesian Flip Chart Media has the potential to facilitate students in learning; and 3) Obstacles in implementing Flip Chart Media in the Indonesian language subject at SDN 1 Sukarara, including 1) Limited Resources, 2) Teacher Readiness Level; 3) Technical Constraints in Using Flip Chart; 4) Varied Student Participation Levels; 5) Lack of Administrative Support; 6) Resistance to Change; and 7) Limited Classroom Physical Conditions.